ФАРҒОНА ВОДИЙСИДА СУҒОРИЛАДИГАН ЕРЛАРНИНГ ТУПРОҚ-ЭКОЛОГИК ҲОЛАТИДАГИ ЎЗГАРИШЛАРНИ БАҲОЛАШ (Scientific journal of the Fergana State University, 2023)
The article analyses the changes of soil-ecological condition of watering lands of Fergana valley, taking into account the evaluations of worked out recommendations.